A comparative evaluation of collagen in ameloblastoma and oral squamous cell carcinoma using picrosirius red staining with polarizing microscopy and CD44v6 immunoreactivity - Sanjay G Thete; Atul Deshmukh; Renu Yadav; Dhirajkumar Umbare; Kanchan N Shinde; Sachin Kandalkar (Wolters Kluwer Medknow Publications, 2023)
Background: Solid multicystic ameloblastoma (SMA) is a locally aggressive, benign odontogenic tumor of odontogenic origin with greater rate of recurrence. Epithelial-mesenchymal interaction plays an important role in tooth morphogenesis that shows complete differentiation of epithelial and ectomesenchymal components to the level of tooth formation. Tumor stroma in ameloblastoma is normal mature collagen that prevents differentiation to the level of tooth formation. Current study evaluates the role of stromal elements in aggressive behavior of SMA using picrosirius red staining with polarizing microscopy and CD44v6 immunohistochemistry (IHC). Objectives: To compare nature of collagen using picrosirius red staining under polarized microscope and IHC expression of CD44v6 marker in SMA and oral squamous cell carcinoma (OSCC). Methods: Thirty blocks were retrieved from departmental archives and subjected to picrosirius red staining and CD44v6 IHC staining. Slides stained with picrosirius red were observed under polarized microscope to report the birefringence pattern. IHC slides were annotated for intensity of staining of tumor cells. Results: In contrast to OSCC's 40% red, 40% yellowish-red, and 20% greenish-yellow birefringence, SMA displayed 87% red, 13% yellowish-red, and 0% greenish-yellow. Compared to OSCC, which had tumor cells stained 9% strongly, 64% moderately, 27% mildly, and 0% negatively, SMA revealed 0% strong, 10% moderate, 60% weak, and 30% negative staining. Conclusion: As opposed to OSCC, which exhibited a greater quantity of greenish-yellow birefringence of immature collagen, SMA showed predominantly red birefringence, which is suggestive of mature collagen with a lack of metastasis. Comparing SMA to OSCC, the lack of significant CD44v6 positivity suggests that there has not been perineural invasion or regional metastases in SMA.